Effect of Chlorine on Incorporation of Helicobacter pylori into Drinking Water Biofilms - Gião, M. S. (American Society for Microbiology (ASM), 2010)
The use of a specific peptide nucleic acid (PNA) probe demonstrated that Helicobacter pylori persisted inside biofilms exposed to low concentrations of chlorine (0.2 and 1.2 mg liter(−1)) for at least 26 days, although no culturable cells were recovered. Coupled with data obtained using viability stains in pure culture, this result suggests that H. pylori can survive chlorination but remain undetectable by culture methods, which can be effectively replaced by PNA hybridization.